2017
DOI: 10.1021/acsami.6b14868
|View full text |Cite
|
Sign up to set email alerts
|

Programmable Shape Recovery Process of Water-Responsive Shape-Memory Poly(vinyl alcohol) by Wettability Contrast Strategy

Abstract: Water-responsive shape-memory polymers (SMPs) are desirable for biomedical applications, but their limited shape recovery process is problematic. Herein, we demonstrate a shape-memory poly(vinyl alcohol) (SM-PVA) with programmable multistep shape recovery processes in water via a wettability contrast strategy. A hexamethyldisilazane (HMDS)-treated SiO nanoparticle layer with varying loading weights was rationally deposited onto the surface of SM-PVA, aiming to create surface-wettability contrast. The varying w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(40 citation statements)
references
References 62 publications
0
40
0
Order By: Relevance
“…Indeed, such materials undergo a glass-rubber transition when in contact with biological fluids with formation of a gel, the dissolution/erosion behavior of which depends on the relevant viscosity and, therefore, on the polymer molecular weight. Particularly, PVA was selected based on both the experience gained on relevant processing via HME and FDM as well as the review of preliminary literature findings on the exhibited water-driven shape memory ability, which relies on its semi-crystalline nature or may be obtained by crosslinking (De Jaeghere et al, 2015, Fang et al, 2017, Melocchi et al, 2015b, Qi et al, 2014. With respect to SMPs already proposed for drug delivery purposes, mainly including newly synthetized crosslinked polymers wanting regulatory approval, the PVA selected offers the advantage of a long-established use and safety profile (Nagahama et al, 2009, Wischke et al, 2009.…”
Section: Design and Fabrication Of Specimensmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, such materials undergo a glass-rubber transition when in contact with biological fluids with formation of a gel, the dissolution/erosion behavior of which depends on the relevant viscosity and, therefore, on the polymer molecular weight. Particularly, PVA was selected based on both the experience gained on relevant processing via HME and FDM as well as the review of preliminary literature findings on the exhibited water-driven shape memory ability, which relies on its semi-crystalline nature or may be obtained by crosslinking (De Jaeghere et al, 2015, Fang et al, 2017, Melocchi et al, 2015b, Qi et al, 2014. With respect to SMPs already proposed for drug delivery purposes, mainly including newly synthetized crosslinked polymers wanting regulatory approval, the PVA selected offers the advantage of a long-established use and safety profile (Nagahama et al, 2009, Wischke et al, 2009.…”
Section: Design and Fabrication Of Specimensmentioning
confidence: 99%
“…In particular, as the temperature required to activate the shape transformation strictly depends on the material glass transition temperature, DSC analyses were initially performed. Indeed, shape shifting phenomena depend on amorphous regions of the polymer gaining mobility when Tg is reached, while permanent shape could be supported by crystalline domains, which would undergo melting at a higher temperature thus acting as net points (Fang et al, 2017). Therefore, evaluating how Tg is affected by the polymer grade, the presence of plasticizer and the interaction with water is of utmost importance because the temporary shape i) must be programmed at Tdef > Tg (in the present case Tdef ≈ Tg + 35 °C), ii) can be preserved keeping the material at T < Tg and iii) is reversed to the original shape at T > Tg.…”
Section: Shape Memory Responsementioning
confidence: 99%
“…Tan et al demonstrated a fast water‐responsive hybrid by incorporating electrospun nanofibrous mats in a thermoplastic polyurethane matrix . In contrast, Fang et al utilized surface modification by depositing varying amounts of hexamethyldisilazane‐treated silica nanoparticles on poly(vinyl alcohol) to achieve water‐responsiveness by creating a surface wettability contrast . In view of such advances, it is crucial to come up with processing techniques to control the actuation duration and further improve the fixation and recovery properties of water‐responsive SMPs.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly to the water adsorption and desorption kinetics [ 9 ], the changes in nanopaper curvature as a function of time can be described by a pseudo-first order kinetic model [ 26 ], expressed as: …”
Section: Resultsmentioning
confidence: 99%